Coat protein gene mediated resistance to Potato virus Y in transgenic tobacco - V.G. MALATHI, M.D. GUPTA; A.1. BHAT, T. MAKESHKUMAR*, A. VARMA, K.K. SINGH (Indian Phytopathology, 2002)
The coat protein (CP) gene and 3’ end untranslated region of Potato virus Y (PVY) were cloned into two plant transformation vectors (pPVSTIII and pBinAR) in both sense and antisense direction. One sense and three antisense constructs (CpS1, CpAS1, CpAS2 and CpAS3) were selected for the transformation of tobacco (Nicotiana tabacum) cvs White Burley and Xanthi via Agrobacterium tumefaciens mediated gene transfer. Analysis of the transformed plants by nucleic acid spot hybridization showed that 37 out of 77 plants were positive for gene incorporation. Southern analysis of the transformed plants confirmed the incorporation of CP gene into host chromosome and in some lines more than one copy number of transgene was obs.erved. Translated protein product of CP gene was, however not detected in any of the transgenic lines. Of the 17 transgenic lines tested for resistance to PVY, five antisense lines were completely resistant as these were not infected up to 30 days, 10 lines (two sense and eight antisense) showed varied degree of resistance and two antisense lines were susceptible. Infection in the resistant lines varied from 13 -56% and in five such lines symptom development was delayed.